2016
DOI: 10.1590/0004-282x20160094
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation to Brazilian Portuguese of the Michigan Neuropathy Screening Instrument: MNSI-Brazil

Abstract: Diabetic sensorimotor polyneuropathy (DSPN) affects approximately 10% of the subjects newly diagnosed 1,2,3 as type 2 diabetes and this percentage can increase by duration, lack of glycemic and cardiovascular complications 3,4,5 . When appropriately treated by restoration of glycemic control 3 , the progression of the DSPN can be delayed and the diabetic ulcers and amputations reduced 3,6 . However, the neuropathy is still the major cause of diabetic foot presenting damaged nerve fibers and this secondary comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
(30 reference statements)
1
11
1
5
Order By: Relevance
“…In this method, when the instrument is applied to the same individual at different times, there should be no difference between the measurements and the correlation should be >0.70 for instrument stability [27]. The test-retest ICC values of the Portuguese and Brazilian Portuguese versions of the MNSI were 0.91 and 0.864, respectively [18,19]. In the present study, the test-retest analysis showed no difference between the measurements and the correlation between the two measurements was 0.97.…”
Section: Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In this method, when the instrument is applied to the same individual at different times, there should be no difference between the measurements and the correlation should be >0.70 for instrument stability [27]. The test-retest ICC values of the Portuguese and Brazilian Portuguese versions of the MNSI were 0.91 and 0.864, respectively [18,19]. In the present study, the test-retest analysis showed no difference between the measurements and the correlation between the two measurements was 0.97.…”
Section: Reliabilitymentioning
confidence: 99%
“…The MNSI has been adapted into many languages such as Portuguese and Brazilian Portuguese [18,19]. A valid and reliable Turkish version of the MNSI will help standardize the assessment of neuropathic patients in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Na segunda etapa foi realizado o exame clínico dos pés por meio do Instrumento de Classificação de Neuropatia de Michigan (Michigan Neuropathy Screening Instrument -MNSI), considerando neuropatia presente em escore igual ou superior a 2,5, com pelo menos um sinal ou sintoma (12) . A classificação do risco de desenvolver o pé diabético foi realizada a partir do instrumento para exame do pé diabético em 3 minutos (13) .…”
Section: Coleta De Dadosunclassified
“…There are currently two Portuguese versions of the MNSI: one was carried out by Barbosa et al, 4 who translated and validated the questionnaire for European Portuguese, and the other by Oliveira et al, 5 who translated and cross-culturally adapted it to Brazilian Portuguese without properly testing the all instrument measurement properties, as it is highly recommended in science. Besides, their back translation was not performed by two persons with the source language as their mother tongue, as it is recommended in Beaton.…”
Section: Introductionmentioning
confidence: 99%
“…21 However, since the translation in the former study was carried out in Portugal, it exhibits semantic, idiomatic, cultural, and conceptual differences from Brazilian Portuguese and, therefore, cannot be used in Brazil. 5 The second study 5 failed to test the Brazilian Portuguese version of the questionnaire, making it impossible to determine whether the translation displays the same measurement properties as the original. In addition, in their cultural adaptation there is no mention to ''agulhadas'', which is a very common and important symptom related to diabetic neuropathy and this is included in the English version, among some other differences to the present cross-cultural adaptation.…”
Section: Introductionmentioning
confidence: 99%